Principles of colour appearance and measurement - Choudhury, Asim Kumar Roy (Woodhead Publishing series in textiles, 2014)
Colour and appearance perceptions are very complex psychological phenomena. Written by one of the foremost authorities in the field, Principles of Colour and Appearance Measurement is a major two-volume work addressing the key topics required to understand the issues and manage colour effectively. The book addresses how objects appear to viewers, how viewers perceive colour, and the major types of instrumentation used to measure colour. Chapters detail the characteristics of light sources and object colour and appearance attributes. They encompass the complexities of human visual perception, including the various causes and types of colour blindness, and other unusual visual phenomena. The book also covers colour measurement instruments and methods, as well as fluorescence and whiteness. Principles of Colour Appearance and Measurement is a comprehensive resource for designers, colour technologists, colour quality inspectors, product developers, and anyone who uses colour in their work.--Provided by publisher.